Secondary Analysis of Public Metagenomic Data Identifies Periodontal Pathogens in the Oral but Not Gut Microbiome - Jaramillo-Echeverry, Adriana (2025)
The oral microbiome, particularly periodontopathogens, may influence the gut microbiome. The aim of this study was to assess the correspondence, diversity, and abundance of periodontopathogenic bacteria in oral and fecal samples from healthy adults. Secondary analyses of 12 public sequences from 6 healthy women, matched by anatomical site (gut and oral cavity), were performed using 16S rRNA-based metagenomics. The sequences were obtained from the BioProject PRJNA834584, published by the Chinese University of Hong Kong, with data generated via Illumina MiSeq. The Shaman application, which relies on Vsearch and DESeq2 for R, along with the Silva database, facilitated the determination of differential abundance and diversity at the species and genus levels between anatomical sites.  After dereplication and removal of singletons and chimeras, 352 OTUs were identified. Taxonomic assignment resulted in 148 genera and 80 species, corresponding to 88.64% and 25.85% of annotations, respectively. The dendrogram displayed two distinct clusters separating oral and faecal samples, and principal coordinate analysis accounted for 53.7% of the variance by anatomical site (Permanova test, p=0.003). The Shannon diversity index was 2.14 (95% CI: 1.55-2.73) for fecal samples and 2.28 (2.03-2.53) for oral samples. The Simpson index was 0.70 (0.53-0.88) for faecal samples and 0.82 (0.76-0.88) for oral samples. Periodontopathogenic bacteria were found exclusively in oral samples, with variations in frequency. No periodontopathogenic species were detected in fecal samples. The human microbiome from two different niches in healthy adults shows distinct bacterial compositions between the oral cavity and the gut, with Bacteroides predominating in faecal samples and Streptococcus in oral samples. Greater richness was observed in faecal samples. Both microbiomes exhibited high bacterial diversity, with no significant differences.